2019
DOI: 10.4049/jimmunol.1900562
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Basis for LILRB Immune Checkpoint Receptor Recognition of HLA-G Isoforms

Abstract: Human leukocyte Ig-like receptors (LILR) LILRB1 and LILRB2 are immune checkpoint receptors that regulate a wide range of physiological responses by binding to diverse ligands, including HLA-G. HLA-G is exclusively expressed in the placenta, some immunoregulatory cells, and tumors and has several unique isoforms. However, the recognition of HLA-G isoforms by LILRs is poorly understood. In this study, we characterized LILR binding to the b2-microglobulin (b2m)-free HLA-G1 isoform, which is synthesized by placent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…However, the question remains whether all splice variants translate into protein. The crystal structures of HLA-G1 and HLA-G2 have been described [ 12 , 13 ], but, to our knowledge, the existence of other HLA-G isoforms has not been confirmed using crystallography. Figure 1 shows the proposed protein composition of HLA-G isoforms based on the presence of specific exons in their mRNA structure.…”
Section: Hla-gmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the question remains whether all splice variants translate into protein. The crystal structures of HLA-G1 and HLA-G2 have been described [ 12 , 13 ], but, to our knowledge, the existence of other HLA-G isoforms has not been confirmed using crystallography. Figure 1 shows the proposed protein composition of HLA-G isoforms based on the presence of specific exons in their mRNA structure.…”
Section: Hla-gmentioning
confidence: 99%
“…The known receptors are leukocyte Ig-like receptor subfamily B member 1 (LILRB1) and member 2 (LILRB2), also known as ILT2 and ILT4, and the killer immunoglobulin-like receptor 2DL4 (KIR2DL4). The ILT2 receptor recognizes the α3 domain of HLA-G in association with β2M, thereby recognizing the HLA-G1 and HLA-G5 isoforms [ 12 , 14 ]. ILT2 is expressed by all monocytes and B cells, but also by subsets of natural killer (NK) cells, T cells, dendritic cells and myeloid-derived suppressive cells (MDSCs) [ 15 ].…”
Section: Receptors Of Hla-gmentioning
confidence: 99%
“…In vitro and in vivo studies have shown that HLA-G dimers are observed for all isoforms except HLA-G3 ( 25 ). Moreover, β 2 m-associated and β 2 m-free dimers of HLA-G1 or HLA-G5 also exist ( 26 28 ). Dimer formation affects the specificity of receptor-HLA-G binding, as dimers exhibit a higher overall affinity to immunoglobulin-like transcript (ILT)2/4 receptors than monomers due to significant avidity effects ( 24 , 28 , 29 ).…”
Section: Molecular Structure Of Human Leukocyte Antigen-gmentioning
confidence: 99%
“…NK cells, T cells, DCs, and decidual macrophages sHLA-G1 Crystal structure [52] sHLA-G1 Crystal structure [53] sHLA-G1 Surface plasmon resonance [35] sHLA-G1 Surface plasmon resonance [54] HLA-G tetramers Tetramer-binding assays [55] mHLA-G1 Cytotoxicity assays [33] ILT4 monocytes, macrophages, and DCs β 2 m-free HLA-G1 dimers Surface plasmon resonance [52] sHLA-G1 Crystal structure [56] sHLA-G1 Surface plasmon resonance [35] HLA-G tetramers Tetramer-binding assays [55] sHLA-G Cell binding assays [57] KIR2DL4 NK cells mHLA-G Binding assays and cytotoxicity assays [36] mHLA-G Cytotoxicity assays [58] mHLA-G Binding assays [59] CD8 CD8 + T cells sHLA-G1 Apoptosis assay [60] CD160 Endothelial cells…”
Section: Ilt2mentioning
confidence: 99%